UNIT 1.23 mtDNA Variation and Analysis Using Mitomap and Mitomaster. Issue 1 (12th December 2013) - Lott, Marie T.; Leipzig, Jeremy N.; Derbeneva, Olga; Xie, H. Michael; Chalkia, Dimitra; Sarmady, Mahdi; Procaccio, Vincent; Wallace, Douglas C.
Abstract: The Mitomap database of human mitochondrial DNA (mtDNA) information has been an important compilation of mtDNA variation for researchers, clinicians, and genetic counselors for the past 25 years. The Mitomap protocol shows how users may look up human mitochondrial gene loci, search for public mitochondrial sequences, and browse or search for reported general population nucleotide variants as well as those reported in clinical disease. Within Mitomap is the powerful sequence analysis tool for human mitochondrial DNA, Mitomaster. The Mitomaster protocol gives step‐by‐step instructions showing how to submit sequences to identify nucleotide variants relative to the rCRS, determine the haplogroup, and view species conservation. User‐supplied sequences, GenBank identifiers, and single‐nucleotide variants may be analyzed. Curr. Protoc. Bioinform . 44:1.23.1‐1.23.26. © 2013 by John Wiley & Sons, Inc.